Financing MSMEs Green Growth, Resource Efficiency and Cleaner Production in East Africa - Albert Mangitia Ongechi; Nebert Ombajo Mandala (European Scientific Journal, ESJ, 2021)
Resource efficiency, including cleaner production and energy efficiency (CP/EE), play an important role in supporting Africa’s sustainable growth in the future. Since the 1990s both the governments and development agencies in Africa have promoted such strategies to help firms reduce their negative environmental impact while enhancing their economic performance. The main objective of this study was first to explore opportunities and constraints for the commercial financing of micro, small and medium enterprises (MSMEs) for resource efficiency and cleaner production (RECP) projects in East Africa (EA), and to develop a sustainable financial scheme for firm-level RECP programs; secondly, to interrogate financing opportunities for RECP advisory services allowing for the growth of the RECP agenda and providing the opportunity to make RECP programs self-sustaining; and thirdly, to increase the use of, and investment in RECP technologies by Enterprises (Industries and MSMEs) in EA. A survey was undertaken across EA and stratified sampling was used to ensure all the partner states were included in the sample. A mixed method approach was used where both primary and secondary data were collected. The sample size comprised of 36 financial institutions and 42 enterprises across the EA region. Key respondents across the industries were interviewed, and a semi–structured questionnaire was used. Quantitative data was analysed by descriptive analysis using SPSS and presented in form of frequency tables. Content analysis was used for the qualitative data and then presented in prose. A hybrid kind of scheme(s) was developed. The study recommends a guarantee scheme whereby the government and or development partners provide guarantee to commercial banks at 50% and the enterprises would be required to raise 50% collateral to unlock funding to enterprises. However, most MSMEs indicated the lack of capacity to raise the 50% collateral hence the study proposes a revolving fund supported by the development funds to set aside a kitty to cater for this category of enterprises. Additionally, a rigorous process has been put in place to implement these two models of financing. Through the study formulation of managerial policy and practice that promote better RECP practices and green growth will be operationalized.